Carbohydrates from Mikania glomerata Spreng tea: Chemical characterization and hepatoprotective effects. (October 2020) - Chaves, Pedro Felipe Pereira; Adami, Eliana Rezende; Corso, Claudia Rita; Milani, Letícia; de Oliveira, Natalia Mulinari Turin; da Silva, Liziane Cristine Malaquias; Acco, Alexandra; Iacomini, Marcello; Cordeiro, Lucimara Mach Côrtes
Abstract: Plant species which have therapeutic purposes are countless, among them is Mikania glomerata Spreng. This plant belongs to the Asteraceae family and is native of the South of Brazil, where its tea is widely used. Since carbohydrates can present diverse biological effects, the aim of this study was to chemically characterize the carbohydrate content of the M. glomerata tea and evaluate its effects on liver function in mice. Carbohydrates were accessed by ethanolic precipitation. After purification, an inulin type fructan (SMG) was characterized. Fructooligosaccharides ranging from GF2 (m/z 543) to GF10 (m/z 1839) were observed in the ethanolic supernatant (MG-ET). Both fractions showed low amounts of protein, phenolic compounds and flavonoids and high amounts of total carbohydrate. In vitro results showed DPPH radical scavenging capacity for both fractions. In vivo results indicated that the fractions could attenuate the alterations in alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, catalase, lipid peroxidation and glutathione levels caused by CCl4 administration. Thus, Mikania glomerata tea shows high carbohydrate content with inulin and fructooligosaccharides as main components. The tested fractions did not produce a hepatotoxic effect per se and protected the liver against CCl4 -induced injuries. Graphical abstract: Image 1